Study of Cardiovascular Malformation in Congenital Rubella Syndrome in Two Tertiary Level Hospitals of Bangladesh - Nazme, Nure Ishrat; Hussain, Manzoor; Hoque, Md Mahbubul; Dey, Arjun Chandra; Das, Ashith Chandra (Bangladesh Journal of Child Health, 2015)
Background: Congenital Rubella infection is a serious disabling problem for children resulting in Congenital Rubella Syndrome (CRS). The exact pattern of the CRS related cardiovascular malformation has not yet been well established in Bangladesh. The objective of this study was to observe the pattern of cardiovascular malformation in Congenital Rubella Syndrome. Methodology: This cross-sectional study was conducted in Dhaka Shishu (Children) Hospital and National Institute of Cardiovascular Diseases (NICVD). Total 40 suspected CRS cases were recruited from both indoor and outpatient departments of the two study hospitals. Serum samples were tested for rubella-specific IgM and IgG, visual and hearing assessment, chest radiography and colour doppler echocardiography were performed at appropriate specialized centres. Results: The mean (±SD) age of the study population (n=40) was 6.6 (±5.7) months (range: 024 months), 68% children were male and 32% were female. Congenital heart disease (CHD) was found in 78% children. Patent ductus arteriosus was the commonest (47.5%) structural defect followed by pulmonary stenosis (22%), atrial septal defect (17.5%) and ventricular septal defect (17%). The chest X-ray of CHD cases showed cardiomegaly in 71% cases and patchy opacity and/or consolidation in 65% cases. Regarding serological assessment of the 37 patients (3 patients rejected blood collection), 60% cases showed IgG positive and 28% cases revealed positive IgM. Conclusions: Various forms of cardiovascular malformation are present in CRS patients. Treatment modalities differ in each type of CHD and its early detection can reduce childhood mortality and morbidity. DOI: http://dx.doi.org/10.3329/bjch.v38i3.22822 Bangladesh J Child Health 2014; VOL 38 (3) :137-141